2019
DOI: 10.2139/ssrn.3319797
|View full text |Cite
|
Sign up to set email alerts
|

Marine DNA Viral Macro-and Micro-Diversity From Pole to Pole

Abstract: Microbes drive most ecosystems and are modulated by viruses that impact their lifespan, gene flow and metabolic outputs. However, ecosystem-level impacts of viral community diversity remains difficult to assess due to classification issues and few reference genomes. Here we establish a ~12-fold expanded global ocean DNA virome dataset of 195,728 60 viral populations, now including the Arctic Ocean, and validate that these populations form discrete genotypic clusters. Meta-community analyses revealed five ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 88 publications
2
41
0
Order By: Relevance
“…58 Nonetheless, recent viral metagenomic studies using NGS technologies and bioinformatic analyses have identified a large number of viruses in environmental samples, including plants and oceans. 59,60 Characterisation of these newly identified viruses may provide new insight into the significance of viruses and virus-mediated processes within global ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…58 Nonetheless, recent viral metagenomic studies using NGS technologies and bioinformatic analyses have identified a large number of viruses in environmental samples, including plants and oceans. 59,60 Characterisation of these newly identified viruses may provide new insight into the significance of viruses and virus-mediated processes within global ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…We mapped the short reads from 223 published marine viral metagenomic samples (29) to the 5539 single amplified genomes (30) Table S4. These virome samples come from 65 Tara stations.…”
Section: Virome Mappingmentioning
confidence: 99%
“…As there are no universal conserved marker genes for phages, we utilized recently published marine datasets (29,30) to demonstrate that PhageBoost can discover previously unseen prophage signals.…”
Section: Superimposition Of Tara Ocean Viral Samples On Single-cell Gmentioning
confidence: 99%
“…In the oceans, the vast majority of biodiversity is conned to the microbial fraction containing prokaryotes and eukaryotic microbes, which represents $60% of the biomass. 5 The Indian mangrove forests comprise about 3.3% of the world's mangroves. It has been predicted that pelagic bacteria are exceptionally abundant, achieving densities of up to 10 6 to 10 9 per mL of seawater.…”
Section: Introductionmentioning
confidence: 99%